PENINGKATAN HASIL BELAJAR SISWA PADA MODEL PEMBELAJARAN INDEX CARD MATCH DI SMP NEGERI 3 MANIAMOLO - Harefa, Darmawan; Sarumaha, Murnihati; Gee, Efrata; Ndruru, Kalvintinus; Ndruru, Mastawati; Telaumbanua, Tatema; Ndraha, Lies Dian Marsa (Unversitas Katolik Santo Thomas, 2021)
The purpose of the implementation of this study was to determine the effect of the index card match learning model on student cognitive learning outcomes in Integrated Science subjects class VIII SMP Negeri 3 Maniamolo in the 2020/2021 Learning Year. This study uses a quantitative approach with a quasi-experimental method. The sample of this research is class VIII-A with 30 students and class VIII-B with 31 students. The instrument used is a learning outcome test which is divided into two, namely the initial test and the final test and documentation. Based on the results of data processing that has been carried out by researchers, the following results are obtained: